Chapter 'Oude drucken ... welcke alle ... ghesien ende gehanteert zijn'' De hulp van Gisbertus Voetius (1641) bij het bepalen van verloren gegane uitgaven van de (gereformeerde) Liturgie - De Jong, Klaas-Willem (Amsterdam University Press, 2022)
The present article is the result of the ongoing research of the project 'The Dynamics of the Classical Reformed Liturgy in the Netherlands: Its Texts and their History'. This Liturgy is recorded in numerous psalm books and Bibles. The question arises how many editions of the Liturgy have not been preserved, or which are not known in publicly accessible collections. To this end, the article analyses a list of forty editions of the Liturgy from the period 1566-1634 that the theologian Gisbertus Voetius included in 1641 in a book entitled Catechisatie Over den Catechismus der Remonstranten. The article examines in particular the extent to which a tried and tested statistical analysis can be helpful in determining the value of this list. The article concludes that the data provided by Voetius not only provides information about a number of specific lost books, but, taking into account a number of uncertain factors, also offers an indication of the probable total number of editions containing the Liturgy that were originally published and are now untraceable.